More Meaningful Real Action: The Passion Curriculum for Self-Exploration and Development - Nazila Puspitasari (Indonesian Journal on Education (IJoEd), 2025)
Based on the assumption that learning that is aligned with students' interests and talents will produce more meaningful and long-term impactful learning experiences, this study investigates how a curriculum approach that explicitly explores and accommodates students' 'passions' is integrated into the design of learning, assessment, and student self-development. The purpose of this study is to understand how a passion-based curriculum is implemented in a high school, and to evaluate its impact on students' motivation, learning engagement, and skill development. This study also aims to contribute to the development of a similar curriculum at Madrasah Aliyah Al-Amiriyyah and open up opportunities for further studies related to the long-term impact on students' careers and quality of life. The research used a qualitative case study involving three high schools that have initiated the implementation of 'passion'-based curriculum elements. Data were collected through in-depth interviews with principals, teachers, students, and parents, observations of the learning process in the classroom, and analysis of curriculum documents and student portfolios. The results show that the implementation of a 'passion'-based curriculum in the study schools involves a variety of strategies, including interest and talent exploration programs, interdisciplinary learning projects oriented to students' 'passions', and a mentoring system that supports the development of individual potential. The findings also revealed significant improvements in learning motivation, student engagement in the learning process, and the development of 21st century skills such as creativity, collaboration, and problem solving. In addition, students demonstrated a deeper understanding of their learning goals and had a clearer career vision. Contribution of Passion-Based Curriculum Development: Exploring Students' Interests and Talents as a Foundation for Meaningful and Long-Term Impactful Learning at Madrasah Aliyah Al-Amiriyyah. This study also paves the way for further research on the long-term impact of passion-based curriculum on alumni career development and quality of life.